Contesting identity through the market: Tourism and indigenous movement in Kasepuhan Ciptagelar, West Java - Nur Widiyanto; Rindha Widyaningsih; Suhartapa (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
This study identifies the interplay between the engagement of Kasepuhan Ciptagelar, an indigenous community inhabiting the state forest in West Java, and tourism development in the area. Practising local spirituality rooted in an indigenous belief, tatali paranti karuhun, while administratively accepting Islam, the people have been struggling to deal with the nearby majority Sundanese who practices Islam and the establishment of the national park covering their living space. The study considers whether a minority group living in an area endowed with both natural and cultural tourism resources consciously chooses tourism as a selected ground to deal with policies which neglect them in terms of religious practices and land policy. Employing the ethnographic method, the study reveals that contesting identity in tourism also means the readiness to accommodate various outside elements. However, the strategy has led the Halimun Salak National Park authority to declare the area as a “special status area” for cultural tourism inside the state park since 2017. The study findings show that after engaging with tourism, various rituals and art performances rooted in the old Sundanese spirituality, which is not officially recognized by the state, can be freely performed for the sake of tourists. In this case, the community is not passive in dealing with external forces but has also enabled its own silent productivity, including its varying consequences.